3D Printing of Frontal-polymerized Multiscale Epoxy Thermoset and Composites. (September 2022) - Zhang, Zimeng; Gao, Chongjie; Liu, Ruochen; Qiu, Jingjing; Pei, Zhijian(ZJ); Wang, Shiren
Abstract: Epoxy thermosets and their composites demonstrate an intensive application due to their high strength, chemical resistance, and lightweight while the conventional manufacturing methods are very difficult to fabricate complex geometry and also time-consuming and energy-intensive. Frontal polymerization based in-situ curing provides an alternative efficient way in the additive manufacturing of epoxy thermosets with both design and manufacturing freedom. However, low reactivity of epoxy resins makes it difficult to integrate frontal polymerization of epoxy resin into energy-efficient additive manufacturing. Carbon nanotubes (CNTs) catalyzed frontal polymerization of epoxy resins afforded a new way to free-form manufacturing of epoxy thermosets with low energy consumption and design flexibility. In this paper, frontal curing of epoxy resins was tuned by CNT catalysation and then integrated to fast printing of multiscale epoxy composites. Specifically, discontinuous CNTs and continuous carbon fibers (c-CF) were integrated to print frontal-cured multiscale epoxy composites. The mechanical tests indicated that the CNTs/c-CF/epoxy thermosets composites demonstrated a tensile strength of 1.2GPa while the CNTs/epoxy thermosets only showed a tensile strength of around 50 MPa. The young's modulus of the CNTs/c-CF/Epoxy thermosets reached 95 GPa, around 9-fold higher than that of the CNTs/Epoxy thermosets. This emerging technology provides a new direction for thermosets and composites manufacturing.